PENGEMBANGAN PENUNTUN PRAKTIKUM ZOOLOGI VERTEBRATA BERBASIS ANDROID PADA MAHASISWA PENDIDIKAN BIOLOGI UIN ALAUDDIN MAKASSAR - Nurcahya Septi Arisma; Ainul Uyuni Taufiq; Syahriani Syahriani; Syamsul Syamsul (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
This study aims to: 1) Develop an android-based Vertebrate Zoology practicum guide for Biology Education students at UIN Alauddin Makassar, 2) Determine the level of validity of the Android-based Vertebrate Zoology practicum guide, 3) determine the practicality of the Android-based Vertebrate Zoology practicum guide, 4) determine the level of practicality of the Android-based Vertebrate Zoology practicum guide. effectiveness of the android-based Vertebrate Zoology practicum guide. This type of research is Research and Development (RnD) with the Tjeer plomp model with four stages: 1) initial investigation, 2) design, 3) realization, 4) test, evaluation, revision. Based on the level of validity of the chest practicum guide in the very valid category, which is worth 1 using the Gregory test matrix. The level of practicality of the practicum guide is in the very practical category with a score of 3.63 using an observation sheet using a guide and a score of 3.83 using an educator response questionnaire. The level of effectiveness of the practicum guide is in the very effective category with a value of 3.66. Thus the android-based Vertebrate Zoology practicum guide meets the valid, practical and effective criteria. So that it can be used in the Biology Education Laboratory of UIN Alauddin Makassar.